2017
DOI: 10.1093/gerona/glx016
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy at Advanced Maternal Age Affects Behavior and Hippocampal Gene Expression in Mouse Offspring

Abstract: There is growing evidence that advanced maternal age is a risk factor for neurological and neuropsychiatric disorders in offspring. However, it remains unclear whether the altered brain programming induced by advanced maternal age is mediated by pre- or postnatal factors. Here, a mouse model was used to investigate whether pregnancy at advanced age may provoke behavioral and brain gene expression changes in offspring. Swiss Albino mice conceived by 3-month-old males and either 15–18-month-old (n = 11) or 3-mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 75 publications
2
24
0
Order By: Relevance
“…Previous studies indicated that C57 female mice display a reproductive decline starting at 6-8 months, which results in decreased pregnancy rate, increased fetal resorption and diminished litter size [27]. Such effects of ageing were also observed by us in an outbred strain [28] and in inbred C57 and BTBR T+ Itpr3tf/J mice [29]. In the present study, one-year-old females supplemented with RES were mated faster than controls.…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies indicated that C57 female mice display a reproductive decline starting at 6-8 months, which results in decreased pregnancy rate, increased fetal resorption and diminished litter size [27]. Such effects of ageing were also observed by us in an outbred strain [28] and in inbred C57 and BTBR T+ Itpr3tf/J mice [29]. In the present study, one-year-old females supplemented with RES were mated faster than controls.…”
Section: Discussionsupporting
confidence: 82%
“…Some existing mechanistic studies have con rmed that the spatial learning capacity of mice at 32-35 weeks is lower than that of mice at 9-12 weeks, which may be related to the decrease in the expression of vitamin D receptor (VDR) in the early embryogenesis process [47]. In addition, compared with 3-month-old mice, 15-18-month-old mice showed anxiety-like behavior, and the gene expression pattern of the hippocampus also changed [48]. We also speculated that late production age may be related to the egg quality [49].…”
Section: Discussionmentioning
confidence: 99%
“…Decline of female reproductive functions over time is characterized by a decrease in oocyte reservoir, low oocyte quality and high risk of pregnancy loss or complications, as widely described in several mammalian species [31][32][33][34][35][36][37][38][39][40]. Mouse models showed that aged females (> 10 months old) are able to produce progeny, however pregnancies are characterized by smaller litter size and increased rate of complications/pregnancy lost when compared to pregnancy outcome in young females [32][33][34].…”
Section: Early Development and Reproductive Outcome In Pregnancies At Advanced Maternal Agementioning
confidence: 99%
“…Regarding post implantation development, an association between AMA and increased risk of pregnancy complications (such as pregnancy loss and fetal malformations, impaired placental development, difficulties in spontaneous parturition, and low birth weight) has been widely described [33,34,[38][39][40]. For example, Woods et al [40] showed that at least two-thirds of fetuses conceived by aged mothers were characterized by fetal growth retardation, cardiac edema, brain and neural tube defects, as well as vascular defects (e.g., dilated dorsal aorta and/or major brain artery).…”
Section: Early Development and Reproductive Outcome In Pregnancies At Advanced Maternal Agementioning
confidence: 99%